The Language of Laconiam Metrical Inscriptions prior to c. 400 BCE - Guijarro Ruano, Paloma (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2015)
In this paper we analyse the language in which metrical inscriptions from Laconia prior to c. 400 BCE are written. More specifi cally, we try to fi nd if the linguistic Ionic model is mainly reproduced or if, on the contrary, a local dialect is used. Once considered the dialect features shared by Laconian epigrams, prose inscriptions from the same region and epic dialect, we conclude that, contrary to a widespread view, they are written in the epichoric dialect and that its local features are not avoided.
Keywords: Epigram; dialect; language; Epic; Laconia.